Global traumatic brain injury intracranial pressure: from monitoring to surgical decision - Zhang, Dan; Sheng, Yanzhi; Wang, Chengbin; Chen, Wei; Shi, Xiaofeng (Frontiers in Neurology, 2024)
Traumatic brain injury (TBI) is a significant global public health issue, heavily impacting human health, especially in low-and middle-income areas. Despite numerous guidelines and consensus statements, TBI fatality rates remain high. The pathogenesis of severe TBI is closely linked to rising intracranial pressure (ICP). Elevated intracranial pressure can lead to cerebral herniation, resulting in respiratory and circulatory collapse, and ultimately, death. Managing intracranial pressure (ICP) is crucial in neuro-intensive care. Timely diagnosis and precise treatment of elevated ICP are essential. ICP monitoring provides real-time insights into a patient's condition, offering invaluable guidance for comprehensive management. ICP monitoring and standardization can effectively reduce secondary nerve damage, lowering morbidity and mortality rates. Accurately assessing and using true ICP values to manage TBI patients still depends on doctors' clinical experience. This review discusses: a Epidemiological disparities of traumatic brain injuries across countries with different income levels worldwide; b The significance and function of ICP monitoring; c Current status and challenges of ICP monitoring; d The impact of decompressive craniectomy on reducing intracranial pressure; e Management of TBI in diverse income countries.We suggest a thorough evaluation of ICP monitoring, head CT findings, and GCS scores before deciding on decompressive craniectomy.Personalized treatment should be emphasized to assess the need for surgical decompression in TBI patients, offering crucial insights for clinical decision-making.